NILAI-NILAI PENDIDIKAN ISLAM DALAM NOVEL SURGA YANG HARUS KU JAGA KARYA SEAN HASYIM (PENDEKATAN PRAGMATIK RESEPTIF) - Syamsul Ma’arif (EDU-KATA, 2020)
This research is based on Islamic education, namely education that developed from the fundamental values contained in the Al-Qur'an and Al-Hadith. Thisstudy is using novel media. While Novel which can be a medium of education is a novel that contains values that educate humans. That is a story that able to educate the mind, imagination and ethics of a child, and develop the potential of knowledge possessed. The purpose of this study are (1) to describe the values of Islamic Education contained in Novel Surga Yang Harus Ku Jaga By Sean Hasyim; (2) to find out the relevance of the values of Islamic Education contained in the Novel Surga Yang Harus Ku Jaga By Sean Hasyim on the education of Muslim communities. The design of this study uses a descriptive qualitative method with a receptive pragmatic approach. The descriptive qualitative method gives attention to natural data, data in relation to the context of its existence. The result of this research is the discovery of the values of Islamic education. First, Tafakur/ remember Allah. Second patience, patience will give someone a chance to read life issues.Third, devote to parents.